Novel N-quaternary coumarin-3-yl-imidazo[1,2-a]pyridines as fluorescent hybrids: Their synthesis and biological evaluation in cancer cells - Karla Armendariz-Barrientos; Luis A. Pérez; Selene Lagunas-Rivera; Yolanda Alcaraz-Contreras; Marco A. García-Revilla; Heriberto Prado-Garcia; Rocío García-Becerra; Miguel A. Vazquez (Results in Chemistry)
Hybrid coumarin-3-yl-imidazo[1,2-a]pyridines were used to synthesize novel derivatives of quaternary salts 5a-c and 6a,b, employing ethyl iodide and benzyl bromide as alkylating agents. The molecular patterns of Total Polar Surface Area (TPSA) coincide with substituent polarity at positions 6 or 7, along with the substituent at the quaternary N. Notably, most polar molecules contain an amino group at position 7, followed by those substituted with −OMe at position 6. Conversely, molecules lacking substituents are the least polar. Despite existing as salts, the polarity of the compounds does not experience a substantial increase. Nonetheless, solubility experiences a notable decrease, particularly for the 6a-c series, due to the potent hydrophobic effect of the benzyl substituent at the N position. A similar phenomenon is observed with the ethyl substituent in the 5a-c series, albeit with a less pronounced hydrophobic impact. To assess the effect of the quaternary hybrid coumarin-3-yl-imidazo[1,2-a]pyridines on proliferation, both breast (MDA-MB-231) and prostate (PC3) cancer cell lines were utilized. The biological assessment of these cancer cell lines demonstrated that compounds 4a, 4c, and 5c exhibit noteworthy antiproliferative effects on MDA-MB-231 (Inhibitory concentration at 50 % (IC50) values of 2.27 µM, 3.76 µM, and 0.113 µM, respectively) and PC3 (IC50 values of 1.03 µM, 0.527 µM, and 0.888 µM, respectively). Furthermore, these same structures demonstrated substantial fluorescence emissions localized within the cytoplasm. Additionally, compounds decreased the G2/M phase of the cell cycle and increased the SubG1 phase. These findings suggest that these novel hybrids have promising applications in cancer treatment.